The perception of transversal skills among students of business administration: Gender gap. Service-learning, gender and skills in higher education - Plaza-Angulo, Juan José; López-Toro, Alberto Antonio (Elsevier, 2024)
Higher education is increasingly oriented towards educating in values, based on the acquisition of practical skills. This has led to the development of active methodologies which complement theory-based learning and classroom lectures. Service-learning integrates ethical and social commitment by applying previously acquired skills and knowledge in real-life situations. This study aims to analyse the self-perception of transversals skills among students of business administration through a service-learning and the possible influence of gender. A questionnaire comprising 57 variables using a Likert scale was administered to a sample of 210 students, the data were analysed, and statistic significance tests were carried out. The results suggest there is a positive relationship between participation in the service-learning activity and the level of skill, especially for ethical and social skills, with significant differences by gender. This work aims to contribute to the consolidation of service-learning as a tool for the acquisition of ethical and social skills at universities, which is so important for future managers of companies and organisations.
Keywords: Enseñanza superior; Voluntariado; Estudiantes universitarios; Higher education; Transversal skills; Gender; Business management education; Service-learning; Volunteering